Computational Logistics: 10th International Conference, ICCL 2019, Barranquilla, Colombia, September 30 - October 2, 2019, Proceedings - Paternina-Arboleda, Carlos; Vo, Stefan (Lecture Notes in Computer Science (11756), 2019)
This book constitutes the proceedings of the 10th International Conference on Computational Logistics, ICCL 2019, held in Barranquilla, Colombia, in September/October 2019. The 27 papers included in this book were carefully reviewed and selected from 49 submissions. They were organized in topical sections named: freight transportation and urban logistics; maritime and port logistics; vehicle routing problems; network design and distribution problems; and selected topics in decision support systems and ICT tools.